Efficacy of Timolol 0.1% Gel and a Prostaglandin Analog in an Unfixed Combination Compared to the Corresponding Fixed Combinations. Issue 5 (September 2013) - Nucci, Carlo; Varesi, Chiara; Martucci, Alessio; Cesareo, Massimo; Cedrone, Claudio; Mancino, Raffaele; Cerulli, Luciano
Purpose: To investigate the intraocular pressure (IOP) reduction with prostaglandin analogs (PGAs)–timolol fixed combinations versus the unfixed combination of the same PGAs and timolol 0.1% in gel-forming carbomer . Methods: Patients with primary open-angle glaucoma (POAG) receiving for at least 4 weeks the fixed combinations of PGA-timolol, administered once a day in the evening (0.005% latanoprost with 0.5% timolol, 0.004% travoprost with 0.5% timolol, 0.03% bimatoprost with 0.5% timolol) were switched to an unfixed combination of the same PGA (once a day in the evening) with timolol 0.1% in gel-forming carbomer (once a day in the morning) for at least 4 weeks. The primary endpoint was to compare efficacy of fixed vs unfixed combinations in lowering IOP. The effects of both regimens on short-term IOP fluctuations were also assessed . Results: A total of 32 patients (64 eyes) fulfilled inclusion criteria: 17 patients received latanoprost-timolol fixed combination, 9 travoprost-timolol fixed combination, 6 bimatoprost-timolol fixed combination. For all considered time periods each unfixed combination induced an IOP reduction significantly higher than the corresponding fixed combination (paired t test: p<0.05 in all measurements). The diurnal IOP reduction was significantly higher during the unfixed combinations (p<0.001). Unfixed combinations significantly decreased IOP diurnal fluctuations and increased the percentage of patients with daily IOP fluctuation ≤ 2 mm Hg . Conclusions: In this pilot study, PGA and timolol seems to be more effective in POAG treatment when administered as unfixed combinations, reducing both IOP and daily fluctuations. The once a day timolol 0.1% gel-forming carbomer may be a valuable option in PGA-timolol unfixed combination regimen .